Gender and limb differences in dynamic postural stability during landing - Wikstrom, E. A.; Tillman, M. D.; Kline, K. J.; Borsa, P. A. (Clinical Journal of Sport Medicine, 2006)
Objective: To determine if gender and limb dominance affect dynamic postural stability and vertical ground reaction force data during jump landings. Secondary objective was to assess the reliability of the dynamic postural stability index (DPSI).